Finland : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Finland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Finland's 2008 Article IV Consultation shows that spillovers from the global turmoil are adversely affecting activity and may weaken the financial system. From a cyclical perspective, a fiscal structural loosening is warranted. Its effectiveness in Finland's small, open economy would be limited in the absence of an EU-wide fiscal package. The authorities have been confident that an EU-coordinated budget expansion is in the works. There has been agreement that loosening should be designed to minimize damage to long-term fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet